Pengaruh Beban Kerja terhadap Loyalitas dengan Kebijakan Tunjangan Kinerja Sebagai Variabel Intervening pada Kantor Imigrasi Kelas 1 TPI Jambi (Jurnal Manajemen Bisnis Digital Terkini, 2026)
This study aims to analyze the effect of workload on employee loyalty at the Class I TPI Immigration Office in Jambi, with performance allowance policies acting as a mediating variable. The research employed a quantitative approach involving 88 respondents selected from the total employee population. Data were collected through structured questionnaires and analyzed using statistical methods to examine both direct and indirect relationships among variables. The results indicate that employees generally perceive their workload as being at a moderate level; however, workload has a significant negative effect on employee loyalty. In contrast, performance allowance policies demonstrate a significant positive influence on loyalty. Furthermore, the findings reveal that performance allowance policies partially mediate the relationship between workload and employee loyalty, indicating their role in mitigating the negative impact of workload. These results suggest that effective performance allowance policies can enhance employee loyalty despite increasing workload demands. Therefore, organizations should balance workload management with fair and performance-based compensation policies to maintain employee loyalty.